Isu-isu utama sebelum, semasa dan selepas PRU 12: satu analisis kandungan blog-blog Politik Malaysia terpilih - Suhaimee Saahar @ Saabar, (Penerbit UKM, 2008)
The result of the twelfth Malaysian General Election was a big surprise to many, especially the Barisan Nasional (BN) coalition government. It won only 140 out of the 220 parliamentary seats contested. Observersattributed the result to various factors, one of which was the cyber campaign launched by bloggers in the internet. Many of these bloggers saw the internet as a space for them to voice out what had been denied by the mainstream media. This paper seeks to analyze the postings on the blogs by focusing on 193 political blogs that were categorized into three main categories, namely the pro-government blogs, the opposition blogs and the neutral blogs. The findings show that 114 political blogs were critical of or oppposed to the government, and only 28 blogs were supportive of the government. Our findings indicate that these political blogs were dominated mainly by Malay bloggers, who tended to use their pseudonyms to protect their real identities. Most of them were male, with the youngsters the most active. The paper concludes by arguing that the cyber space has now emerged as a main platform for political observers to share information and to speak more freely and more critically about Malaysian politics.